Strategic marketing planning for radio stations in Lesotho - Maliehe, Makhakhe (University of the Free State)
This research study advocates that radio stations in Lesotho should make full use of the benefits offered by marketing both as a philosophy and a business function. The research study also recommends that the radio stations in Lesotho use the strategic marketing planning steps and approach that have been prescribed throughout this project, that is, the development of a mission statement, corporate objectives, situation analysis, competitor analysis, and marketing objectives.
Thesis (Ph.D.(Business Management))--University of the Free State, 2007
Keywords: Radio broadcasting -- Lesotho -- Marketing; Radio broadcasting -- Lesotho -- Management; Marketing -- Planning